O design atitudinal como acionador da comunicação corporal - Santos, Suzana Suguimori (2016)
With the regulation of the designer as a profession, it has been proposed a series of discussions about the responsibility and the designer's role to its users. In this context arises the attitudinal design. The purpose of this master thesis is to analyze this design genre, drawing attention to the ways the new professionals deal with the perception and communication of the body. The main hypothesis is that by abandoning some dichotomies present in classic studies of ergonomics, attitudinal design began to engender, in fact, new attitudes not only from the relations between subject and object, but triggering new ways of life. The research methodology combines literature a few case studies. As theoretical foundation meets specific titles as the work of Lucy Niemeyer (2008), debates on "good design" proposed by Rams (1970), about the "design good" developed by Mizanzuk Portugal and Beccari (2013); and emotional ergonomics from Claudia Mont'Alvão (2008). The corpomídia theory of Katz and Greiner (2013) highlights the bridges with the field of communication and underlies the debate, particularly with regard to problematize the dualisms body-mind and reason-emotion, which surround the subject and not usually associated with each itself. The expected result is to collaborate with these debates, highlighting the importance of communication theories, little present in discussions regarding the design